IH activity is increased in populations of slow versus fast motor axons of the rat - Lorenz, Chad; Jones, Kelvin E. (Frontiers in Human Neuroscience, 2014)
Much is known about the electrophysiological variation in motoneuron somata across different motor units. However comparatively less is known about electrophysiological variation in motor axons and how this could impact function or electrodiagnosis in healthy or diseased states. We performed nerve excitability testing on two groups of motor axons in Sprague-Dawley rats that are known to differ significantly in their chronic daily activity patterns and in the relative proportion of motor unit types: one group innervating the soleus (“slow motor axons”) and the other group innervating the tibialis anterior (“fast motor axons") muscles. We found that slow motor axons have significantly larger accommodation compared to fast motor axons upon application of a 100 ms hyperpolarizing conditioning stimulus that is 40% of axon threshold (Z = 3.24, p = 0.001) or 20% of axon threshold (Z = 2.67, p = 0.008). Slow motor axons had larger accommodation to hyperpolarizing currents in the current-threshold measurement (-80% Z = 3.07, p = 0.002; -90% Z = 2.98, p = 0.003). In addition, we found that slow motor axons have a significantly smaller rheobase than fast motor axons (Z = -1.99, p = 0.047) accompanied by a lower threshold in stimulus-response curves. The results provide evidence that slow motor axons have greater activity of the hyperpolarization-activated inwardly rectifying cation conductance (IH) than fast motor axons. It is possible that this difference between fast and slow axons is caused by an adaptation to their chronic differences in daily activity patterns, and that this adaptation might have a functional effect on the motor unit. Moreover, these findings indicate that slow and fast motor axons may react differently to pathological conditions.